2001
DOI: 10.1097/00007890-200106270-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Donor Age on Liver Transplantation: Influence of Donor Age on Early Liver Function and on Subsequent Patient and Graft Survival

Abstract: Advanced donor age is associated with lower graft and recipient survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
2
8

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(101 citation statements)
references
References 22 publications
6
85
2
8
Order By: Relevance
“…2,[15][16][17][18][19] This incidence is similar to the one observed for our SAP group. It is worth emphasizing that the prevalence of PNF, and consequently of graft/patient losses in the SAP group, are probably overestimated due to the small sample size.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…2,[15][16][17][18][19] This incidence is similar to the one observed for our SAP group. It is worth emphasizing that the prevalence of PNF, and consequently of graft/patient losses in the SAP group, are probably overestimated due to the small sample size.…”
Section: Discussionsupporting
confidence: 90%
“…2 On these grounds, we defined suboptimal livers as those with 1 major negative factor and/or at least 2 minor factors. This definition, based on several studies published in recent years, 2,[6][7][8][9][10][11][16][17][18][19][20] revealed a statistically significant impact on post-LT graft and patient survival rates in a retrospective analysis of our last 400 cases (our unpublished data).…”
Section: Discussionmentioning
confidence: 78%
“…This observation supports recent reports from European and American series that advanced donor age negatively impacts on graft and patient survival among HCV-infected liver transplant recipients. [11][12][13] This is in contrast to patients who received a liver transplant for non-HCV related end-stage liver disease where donor age appeared not to affect prognosis. 11 Therefore, it is apparent that similar to the pretransplant setting, age at the time of HCV infection acquisition is an important determinate of disease progression; however, it is not entirely clear the mechanisms by which donor age contribute to graft injury.…”
Section: Discussionmentioning
confidence: 90%
“…3,10 Recently, advanced donor age has been recognized to adversely influence the posttransplant course among HCV liver transplant recipients. [11][12][13] In Australia and New Zealand, the HCV-infected cohort of patients tend to come from a heterogeneous ethnic background. This offers a unique opportunity to analyze predictors of outcome in a population of HCV liver transplant recipients, with a diverse mode of HCV acquisition and a broad genotype distribution.…”
Section: H Epatitis C Virus (Hcv)-related Liver Disease Is Amentioning
confidence: 99%
“…Donor age of more than 70 years, however, was found to be associated with lower patient and graft survival. 13 In contrast to other organs, the liver may be more immune to senescence, particularly in the otherwise healthy person. This is possibly because of the liver's large functional reserve, regenerative capacity, and dual blood supply, which exceeds its metabolic needs.…”
Section: Donor Agementioning
confidence: 99%